Multivalent counterions diminish the lubricity of polyelectrolyte brushes - Yu, Jing (2020)
Polyelectrolyte brushes provide wear protection and lubrication in many technical, medical, physiological, and biological applications. Wear resistance and low friction are attributed to counterion osmotic pressure and the hydration layer surrounding the charged polymer segments. However, the presence of multivalent counterions in solution can strongly affect the interchain interactions and structural properties of brush layers. We evaluated the lubrication properties of polystyrene sulfonate brush layers sliding against each other in aqueous solutions containing increasing concentrations of counterions. The presence of multivalent ions (Y3+, Ca2+, Ba2+), even at minute concentrations, markedly increases the friction forces between brush layers owing to electrostatic bridging and brush collapse. Our results suggest that the lubricating properties of polyelectrolyte brushes in multivalent solution are hindered relative to those in monovalent solution.